2018
DOI: 10.1111/1467-9566.12733
|View full text |Cite
|
Sign up to set email alerts
|

Fit to father? Online accounts of lifestyle changes and help‐seeking on a male infertility board

Abstract: The reproductive realm is routinely viewed as a feminised space requiring women's commitment and labour. By contrast, men's procreative contributions and 'reproductive masculinity' is represented as unproblematic, with men assumed to be fertile across the lifespan. Recent scientific research has, however, cast doubt over these longstanding assumptions, suggesting that a link does exist between 'lifestyle' factors and male fertility. The notion that fertility can be improved with effort (for both women and men)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…Previous research, including our own (Hanna and Gough , , , Hanna et al . ), into men's experiences of infertility has focused on men's experiences of infertility in a broad sense rather than focusing specifically on a category of diagnosis. This is partly in order to be inclusive, in that infertility in heterosexual relationships is a ‘joint endeavour’, but also due to the difficulties of recruiting men to talk about a stigmatised issue among men (which Dolan et al .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research, including our own (Hanna and Gough , , , Hanna et al . ), into men's experiences of infertility has focused on men's experiences of infertility in a broad sense rather than focusing specifically on a category of diagnosis. This is partly in order to be inclusive, in that infertility in heterosexual relationships is a ‘joint endeavour’, but also due to the difficulties of recruiting men to talk about a stigmatised issue among men (which Dolan et al .…”
Section: Methodsmentioning
confidence: 99%
“…A small, but growing, body of evidence shows that many men find infertility highly challenging and are deeply invested in the achievement of conception (Hanna and Gough , Hanna et al . ). Medical professionals are also seen to ‘shield’ men and their masculinity from the realities of infertility, both through their discourse and practice (Barnes ), but in doing so the notion of fertility as feminised is further reinforced.…”
Section: Introductionmentioning
confidence: 97%
“…2017, Hanna et al . 2018). What distinguished these two men from the others was an overall high level of fertility awareness, which could be traced back to a general high health awareness and familiarity with the health system, including sexual and reproductive health care.…”
Section: Resultsmentioning
confidence: 99%
“…2017, Hanna and Gough 2017, Hanna et al . 2018, Throsby and Gill 2004, Tjørnhøj‐Thomsen 2009, Webb and Daniluk 1999), men’s thoughts about their own fertility is relatively seldom in focus.…”
Section: Introductionmentioning
confidence: 99%
“…A Leeds research team recently studied how men have responded to this, by analysing a men's online infertility discussion forum board. 3 They found that 'lifestyle work' is construed as crucial for achieving conceptionand as a means to demonstrate men's commitment to the goal of parenthood. Perhaps in years to come, 'fitness to father' will be part of our lexicon and thinking.…”
mentioning
confidence: 99%